Economic production quantity model based on extended cost parameters for imperfect process and defective items - Shahraki, Mohammad Reza (2011)
The inventory includes the elements to construct the products that finally will appear as completed goods. The main purpose for the inventory management is effectively utilizing inventories in the manufacturing system to meet customer requirements and bring about the minimum total cost. The classic Economic Production Quantity (EPQ) model is a mathematical model, which determines the lot sizing in a production process so that minimizes the total inventory holding cost and set up cost. The classic EPQ model is assumed that the product quality is always perfect; therefore, the quality cost is not considered as an issue to influence the production lot size. This research aims to extend the existing body of knowledge on the imperfect-quality inventory problem by developing a new inventory model that relaxes some of the previous common assumptions of the EPQ models. The main objective is to minimize the total cost of inventory and quality in a manufacturing system with a single product, and a batch production process. The proposed EPQ model identifies the costs that exist because of poor quality and their effects on the optimal lot size and total cost. The sensitivity analysis is employed to show changes in the optimal production lot size and total cost from variations in the various parameters of the proposed EPQ model. The statistical hypothesis tests demonstrated that the total cost of the proposed EPQ model significantly less than previous EPQ models. The results indicated that the production rate, demand rate, holding cost of returned items, scrap rate, defective rate, warranty cost, lost sale cost, lost sale cost, and holding cost of scrap items have extensive effect on the total cost of manufacturing system.